Desain Turbin Angin Horisontal untuk Area Kecepatan Angin Rendah dengan Airfoil S826 - Setiadi Wira Buana; Putty Yunesti; Guna Bangun Persada; Abdul Muhyi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
This research aims to determine performance of turbine rotor performance with a single rotor blade model with a diameter of 0.6 m that has been developed by NORCOWE, while for turbine rotor blades used is the NREL S826 airfoil series. The wind turbines are operated at wind speed intervals of 1-5 m / s. This parameter will also present data in the form of the optimal point of wind turbine rotation and rotor rotation speed. The pitch angles used are 25 °, 30 °, and 35 °. The pitch angle that affects the value of the ideal rotational speed with the highest optimization for the horizontal airfoil turbine S826 is 30 ° with a wind speed of 5 m / s and a rotation of 570 RPM. This is because the greater the pitch angle of the installation, the easier it will be to experience speed trimming but is vulnerable to too large an angle of attack that causes a stall.